Edupreneurship 4.0: Eksplorasi Strategi Pembelajaran Inovatif Pendidikan Bahasa Arab di Era Digital - Novitasari, Ardina; Sabarudin; Nurhapsari Pradnya Paramita (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
Edupreneurship is an innovative approach that integrates entrepreneurship education with educational values. The combination of these two different fields is a response to the demands of the times. This study aims to examine and describe innovative learning strategies applied to students of the Arabic Language Education Study Program. The study was conducted with a qualitative descriptive approach exploring lecturers' strategies in internalizing edupreneurship values ​​through the use of English as the language of instruction and assignments. Data collection techniques were interviews, observation and documentation. Data analysis used the Miles & Huberman data condensation, data presentation, and verification techniques. One of the innovations carried out was the use of a digital platform from the Wadhwani Foundation to support the development of students' entrepreneurial assignments and skills. The results of the study showed that this strategy had an impact on the growth of students' entrepreneurial interests and abilities amidst advances in digital technology. The integration of edupreneurship with digital branding is a new model in learning development. Internalization of entrepreneurial values ​​strengthens the creative and productive mindset of Arabic Language Education students. The use of English and Arabic in the learning process also improves multilingual communication skills and mastery of digital marketing. This study concludes that innovation in edupreneurship-based learning strategies is effective in developing students' academic and practical competencies.